Development of a loop‐mediated isothermal amplification assay for rapid and sensitive detection of Sporisorium scitamineum in sugarcane. (12th January 2016) - Shen, W.; Xu, G.; Sun, L.; Zhang, L.; Jiang, Z.
Abstract: Smut disease caused by Sporisorium scitamineum is one of the most destructive sugarcane diseases worldwide. The pathogen spreads primarily through infected sugarcane setts, and hence, the use of disease‐free planting materials is essential for preventing disease development in the field. In this study, a species‐specific loop‐mediated isothermal amplification (LAMP) assay was developed for rapid and accurate detection of S. scitamineum . Based on the differences in internal transcribed spacer (ITS) sequences of S. scitamineum, a set of four species‐specific primers, F3, B3, FIP and BIP, were designed by using a panel of fungal and bacterial species as controls. After optimization of the reaction conditions, the detection limit of LAMP assay was about 2 fg of the S. scitamineum genomic DNA in 25 µL reaction solution, 100‐fold lower than that of conventional polymerase chain reaction. The assay showed high specificity to discriminate all S. scitamineum isolates from nine other fungal and bacterial pathogens. The LAMP assay also detected smut infection from young sugarcane leaves with no visible smut‐disease symptoms. The findings from this study provide a simple, highly sensitive, rapid and reliable technique for early detection of S. scitamineum, which may be useful for sugarcane quarantine and production of smut‐free seedcanes. This is the first report of LAMP‐based assay for the detection of S. scitamineum in sugarcane.